The impact of impatience on customer loyalty and satisfaction - Rannveig Guðmundsdóttir 1989- (2015)
In managing business the relationship with customers is of the utmost importance. One of the biggest goals for those who offer products or services is to be the customer’s first choice. To be someone’s first choice depends on many different variables. Some variables are known to in-fluence the lifetime value of the customer, such as price, but what about non-financial variables that can be just as important? This study will see if and how impatience can influence loyalty or satisfaction. Another question answered will be if it is possible to evaluate in cost how much loss follows an unhappy customer. This was evaluated from literature and studies available and from an extensive survey conducted in two call centres from two companies in Iceland, one bank and one power company. Almost one thousand people participated and gave their answers that either indicated that they were patient or impatient. The customer were categorised based on their patience level and whether they received service or abandoned the queue. Then each category was arranged by their loyalty and satisfaction levels. The next step was to compare each category to each other for each question to see whether the categories could be differentiated from each other. This was done with a two sample t-test that returned the test decision for the null hypothesis that the data in the two compared samples came from independent random samples, i.e. could be distinguished from each other. The results showed how impatience influences loyalty and satisfaction for both companies. For loyalty there is a clear impact from impatience for three categories while one is not so clear cut. The results for satisfaction do not show as much of a correlation between satisfaction and the impatience categorisation. Thus impatience has real impact on loyalty and satisfaction. Impa-tience has also an incremental effect on customer loyalty but this cannot be established for satisfaction. This thesis puts forth ideas of methods for cost evaluations that take into account the ...